2009
DOI: 10.1186/1471-2164-10-347
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of next generation sequencing technologies for transcriptome characterization

Abstract: BackgroundWe have developed a simulation approach to help determine the optimal mixture of sequencing methods for most complete and cost effective transcriptome sequencing. We compared simulation results for traditional capillary sequencing with "Next Generation" (NG) ultra high-throughput technologies. The simulation model was parameterized using mappings of 130,000 cDNA sequence reads to the Arabidopsis genome (NCBI Accession SRA008180.19). We also generated 454-GS20 sequences and de novo assemblies for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
158
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(168 citation statements)
references
References 48 publications
8
158
0
2
Order By: Relevance
“…under the HS. Very high levels of upregulation of RCA-A has been reported in response to HS in wheat (Wan et al, 2008), which is concurrent with our observations. Different mechanisms involving signaling molecules, chaperones, TFs, and other SAGs has been reported to be the reason behind the wide-thermotolerance diversity in wheat (Qin et al, 2008), similar to our present findings.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…under the HS. Very high levels of upregulation of RCA-A has been reported in response to HS in wheat (Wan et al, 2008), which is concurrent with our observations. Different mechanisms involving signaling molecules, chaperones, TFs, and other SAGs has been reported to be the reason behind the wide-thermotolerance diversity in wheat (Qin et al, 2008), similar to our present findings.…”
Section: Discussionsupporting
confidence: 93%
“…HD2329 under the control and HS-treated conditions. Earlier, Roche GS-FLX 454 was the most widely used platform for de novo transcriptome sequencing, due to its long read length in different organisms, for example, ginseng (Sun et al, 2010), A. thaliana (Wall et al, 2009), and maize (Vega-Arreguin et al, 2009). The Illumina transcriptome was mainly used for the sequencing of organisms whose genome was sequenced .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, normalized cDNA libraries have still been useful in some cases to this end (for example, Schwarz et al, 2009;Ekblom et al, 2010). When planning the experiment it is also valuable to note that there is a trade off between the cost of normalization and the cost of sequencing (Wall et al, 2009). As sequencing technology keeps improving and the quantity of sequence yield increases, cDNA normalization may soon be superfluous for transcriptome characterization, as a single sequencing run will be able to cover the complete transcriptome of the sampled tissue, regardless of the distribution of transcript abundances.…”
Section: Transcriptome Characterizationmentioning
confidence: 99%
“…However, 454 sequencing presents slightly higher rates of sequencing errors compared with competing technologies (see Table 1), especially in homopolymers (see Glossary) (Huse et al, 2007). Simulation experiments have shown that when there is no reference genome available, a combination of different NGS technologies may be most cost effective for transcriptome characterization (Wall et al, 2009). …”
Section: Epigeneticsmentioning
confidence: 99%